Czy Konstytucja Rzeczypospolitej Polskiej wymusza na ustawodawcy ustawową regulację struktury organizacyjnej i właściwości sądów powszechnych? - Banaszak, Bogusław (Studia Prawa Publicznego, 2020)
The Constitution of the Republic of Poland does not define in a comprehensive manner the matter to be standardized in laws and grants the legislator considerable freedom in determining their content. In view of the subject matter of this opinion, based on views founded on the doctrine of Polish constitutional law and on the jurisprudence of the Constitutional Tribunal and the Supreme Court, it can be concluded that the legislator should regulate by law, among other matters, the following matters reserved for statutory regulation (the principle of exclusivity of the act): regulations concerning citizenship and the rights, freedoms and duties of the individual, as well as the basic competences, principles of how public authorities are organised and function. On the basis of this assumption, it was examined whether there is any indication to the legislator from the constitutional norms relevant to the judicial authority. The following were taken into account: the right to a fair trial (Article 45), the principle of the separateness and independence of the judiciary (Article 173), the principle of bi-instantiality of court proceedings and the principle of statutory determination of the system and jurisdiction of courts (Article 176), the principle of the presumption of competence being assigned to common courts (Article 177), and the principle of the non-removability and non-transferability of judges (Article 180). On the basis of an analysis of these constitutional norms, it was concluded that the Constitution of the Republic of Poland enforces statutory regulation of the organisational structure and the material, local and appeal jurisdiction of common courts, and only allows for entrusting specific matters to be regulated by executive bodies by means of a regulation. In the event of any doubts as to whether a given case should be classified into the category of specific matters, the principle of exclusivity of the Act applies.